THE WORKSHOP OF LAECANIUS AT FAŽANA: Some recent testimonies - Starac, Alka (Rei Cretariae Romanae Fautorum Acta, 2024)
The main subject of this paper is the activity of the Laecanius workshop in the light of some recent unpublished discoveries in Fažana and the nearby site of Dragonera.